Design and assessment of in-vehicle auditory alerts for highway-rail grade crossings. (April 2019) - Landry, Steven; Jeon, Myounghoon; Lautala, Pasi; Nelson, David
Highlights: Train-vehicle collisions at highway-rail grade crossings continue to be a major issue. Thirty-one participants evaluated a pool of potential in-vehicle auditory alerts (IVAAs). A statistical model was made describing the relationship between acoustic parameters and psychological dimensions. Twenty participants drove in a simulator with four types of crossing signage with/without IVAAs. IVAAs reminded drivers of how to comply at crossings and had a lasting effect even after the IVAAs were removed. Abstract: Train-vehicle collisions at highway-rail grade crossings (RR crossings) continue to be a major issue in the US and across the world. To prevent several decades of safety improvements from plateauing, experts are turning towards novel warning devices that can be applied to all crossings with minimal cost. One of the potential approaches is in-vehicle auditory alerts (IVAAs) which are implementable with today's technology and could potentially complement the existing warnings in a cost effective manner. Study 1 collected subjective data on a pool of potential in-vehicle auditory alerts from 31 participants. Study 2 recruited 20 participants to drive in a medium fidelity driving simulator with and without IVAAs for RR crossings. Results suggest IVAAs inform and remind drivers of how to comply at RR crossings, and have a lasting effect on driver behavior after the IVAA is no longer presented. Compliance scores were highest among combination RR crossing visual warnings, such as crossbucks featuring STOP or YIELD signs. Compliance was lowest for crossbucks alone and active gates in the off position. IVAAs had the largest impact on compliance scores at crossbucks and gates. The discussion includes implications for designing IVAA systems for RR crossings, the limitations of the study, and the participants' perception of the novel warning type.